On the Validity and Benefit of Manual and Automated Drift Correction in Reading Tasks - Naser Al Madi (Journal of Eye Movement Research, 2025)
Drift represents a common distortion that affects the position of fixations in eye tracking data. While manual correction is considered very accurate, it is considered subjective and time-consuming. On the other hand, automated correction is fast, objective, and considered less accurate. An objective comparison of the accuracy of manual and automated correction has not been conducted before, and the extent of subjectivity in manual correction is not entirely quantified. In this paper, we compare the accuracy of manual and automated correction of eye tracking data in reading tasks through a novel approach that relies on synthetic data with known ground truth. Moreover, we quantify the subjectivity in manual human correction with real eye tracking data. Our results show that expert human correction is significantly more accurate than automated algorithms, yet novice human correctors are on par with the best automated algorithms. In addition, we found that human correctors show excellent agreement in their correction, challenging the notion that manual correction is “highly subjective”. Our findings provide unique insights, quantifying the benefits of manual and automated correction.